Kajian Teologis Restorasi Pondok Daud Sebagai Fondasi Misi Di Indonesia Menurut Kisah Para Rasul 15 - Manalu, Regen Junior; Sinaga, Risma Sugianti; Pasaribu, George Rudi Hartono; Lumban Gaol, Lidya; Hutagaol, Monalisa (JURNAL TABGHA, 2026)
The concept of the Restoration of the Tabernacle of David is often interpreted in contemporary Indonesian Pentecostal and charismatic churches as the recovery of praise, worship, music, and prayer. Although this liturgical emphasis is important, such a reduction tends to obscure the missional argument embedded in Acts 15:16–17, where James cites Amos 9:11–12 in the context of the Jerusalem Council. This article aims to examine the theological relationship between the Restoration of the Tabernacle of David and the foundation of the church’s mission among the nations. This study uses a qualitative library research method through textual-theological analysis of Acts 15:13–21 and Amos 9:11–12, supported by New Testament exegesis, Pentecostal theology, and missiological literature. The main finding shows that the restoration motif in Acts 15 does not primarily refer to the rebuilding of a physical structure or the recovery of a worship model, but to God’s salvific act of forming an inclusive covenant community in Christ. Thus, the Restoration of the Tabernacle of David functions as a theological foundation for universal mission, reconciliation, and ecclesial participation in Indonesia’s plural society. The study concludes that Pentecostal worship must be read together with Spirit-empowered mission.